Inovasi Pelayanan Publik Melalui Aplikasi Sentuh Tanahku Dalam Meningkatkan Akses Informasi Pertanahan Di Kantor Pertanahan Kabupaten Sampang - Jaka Dwi Sasmita; R. Rukhiyat Surahman (Aspirasi: Jurnal Ilmiah Administrasi Negara, 2026)
This study was motivated by the urgent need for transparency in land information in Sampang Regency to minimize land mafia practices and agrarian conflicts, given the large number of unregistered land parcels. Although there have been digitization efforts through the Sentuh Tanahku application, the level of public acceptance remains relatively low. There is a significant gap between the innovative features provided and the uneven outreach efforts, where the lack of dissemination of this information directly impacts the public’s limited understanding of the app’s functions and benefits in protecting their land rights. The purpose of this study is to examine public service innovations through the Sentuh Tanahku app in improving access to land information at the Sampang Regency Land Office. The research method employed was qualitative, specifically a case study. Data collection techniques included in-depth interviews with Land Office staff and community users, as well as document analysis. Research findings based on Everett M. Rogers’ innovation adoption theory indicate that, theoretically, this application meets the criteria of relative advantage, compatibility, and observability. However, its effectiveness is hindered by technical complexity in account verification and system stability. Additionally, the trialability phase has not been widely implemented because outreach efforts have not been maximized and the public’s readiness to independently adopt digital technology remains low, resulting in a smaller number of verified users in Sampang Regency compared to other regions in East Java.